Does obstructive sleep apnea affect exercise capacity and the hemodynamic response to exercise? An individual patient data and aggregate meta-analysis. (June 2019) - Berger, Mathieu; Kline, Christopher E.; Cepeda, Felipe X.; Rizzi, Camila F.; Chapelle, Céline; Laporte, Silvy; Hupin, David; Raffin, Jérémy; Costes, Frédéric; Hargens, Trent A.; Barthélémy, Jean-Claude; Roche, Frédéric
Summary: Obstructive sleep apnea (OSA) has been linked to altered cardiovascular response to exercise. A systematic review and individual patient data (IPD) meta-analysis were conducted to assess whether OSA patients present reduced exercise capacity. PubMed, Embase and Web of Science were searched until September 2018. Studies which performed sleep recording in both OSA patients and controls and measured maximal oxygen consumption (VO2peak ) via a maximal exercise test were included. IPD were provided for five trials upon the 18 eligible (N = 289) and a two-stage IPD meta-analysis model was used, allowing to standardize the apnea cutoff and adjust for confounders. IPD meta-analysis demonstrated that moderate to severe OSA patients had similar VO2peak (mean difference: −1.03 mL·kg −1 min −1 ; 95% CI: −3.82 to 1.76; p = 0.47) and cardiovascular response to exercise compared to mild or non-OSA patients. By contrast, aggregate data (AD) meta-analysis including the 13 trials for which IPD were unavailable (N = 605) revealed that VO2peak was reduced in OSA patients compared to controls (mean difference: −2.30 mL·kg −1 min −1 ; 95% CI: −3.96 to −0.63; p < 0.001) with high heterogeneity. In conclusion, IPD meta-analysis suggests that VO2peak and the cardiovascular response to exercise are preserved in moderate to severe OSA patients while AD meta-analysis suggests lower VO2peak in severe OSA.